2014
DOI: 10.1039/c4ra05243a
|View full text |Cite
|
Sign up to set email alerts
|

Easy approach to synthesize N/P/K co-doped porous carbon microfibers from cane molasses as a high performance supercapacitor electrode material

Abstract: In this study, we demonstrate a simple and low cost method to synthesize N/P/K co-doped porous carbon microfibers (CMFs) from a sugar-rich byproduct (cane molasses) as the precursor material. A two-step method for the synthesis of N/P/K co-doped porous CMFs involving electrospinning of precursor material followed by simple carbonization at various temperatures (773.15-1173.15 K) was successfully applied. The N/P/K co-doped porous CMFs exhibited high specific surface area ($580 m 2 g À1 ) andhierarchical porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…25 The breakdown of polysaccharide molecules is probably produced until $600 C (18.1 wt% mass loss), as indicated by the continuous weight loss observed in the TG curve, in agreement with a previous study on sugarcane molasses. 26 In addition, this latter work indicated that the weight loss was negligible from 500 to 700 C and that no weight loss was observed up to 900 C. 26 In contrast, our TG/ DTG curves presented two steps between $600 and 758 C and above 758 C with no negligible weight loss values of 3.6 and 7.4 wt%, respectively. Such unexpected stages appearing above 600 C will be explained in detail hereinaer.…”
Section: Samplementioning
confidence: 76%
See 1 more Smart Citation
“…25 The breakdown of polysaccharide molecules is probably produced until $600 C (18.1 wt% mass loss), as indicated by the continuous weight loss observed in the TG curve, in agreement with a previous study on sugarcane molasses. 26 In addition, this latter work indicated that the weight loss was negligible from 500 to 700 C and that no weight loss was observed up to 900 C. 26 In contrast, our TG/ DTG curves presented two steps between $600 and 758 C and above 758 C with no negligible weight loss values of 3.6 and 7.4 wt%, respectively. Such unexpected stages appearing above 600 C will be explained in detail hereinaer.…”
Section: Samplementioning
confidence: 76%
“…Capacitance values of $172 F g À1 at 1 A g À1 current density were reported in a former work, in which electrospun carbon microbres obtained from cane molasses and 1.5 M tetraethyl ammonium tetrauoroborate in acetonitrile electrolyte were used. 26 M-750 and M-900 carbons exhibited specic capacitance values of $13 and 9 F g À1 , respectively, at the same current density, but their surface areas were considerably lower (8 and 102 m 2 g À1 , respectively) than those of the electrospun carbon bres (580 m 2 g À1 ) and different electrolytes were also used.…”
Section: Samplementioning
confidence: 99%
“…[1][2] The key part of a supercapacitor is the electrode material, which predominantly depends the charge storage performance. [5][6][7][8][9][10] During the past several years, various carbon materials, including activated carbon, [11][12][13] carbon nanotubes, [14][15][16] and graphene, [17][18][19][20] have been investigated for use in supercapacitors. Carbon-based materials are not only used in electrochemical double layer capacitors for charge storage, but also employed in pseudocapacitors for improving the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the solutions were prepared by diluting the concentrated solution by mass taking into account Archimedes force correction. Molar concentrations of solutions prepared were calculated by the equation (1).…”
Section: Methodsmentioning
confidence: 99%
“…Non-aqueous electrolyte solutions are widely used in electrochemical energy storage devices, such as supercapacitors (SCs) with porous nano-carbon electrodes [1]. Non-aqueous solutions of tetraalkylammonium salt-based electrolytes were used to test samples of porous carbon electrodes in SCs [2].…”
Section: Introductionmentioning
confidence: 99%